UNLOCKING MEANING: VISUAL SEMIOTIC ANALYSIS IN ANIMATION - Mahalingam, Malini; Daniel, Lakshmi Priya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explains the application of visual semiotic analysis in animation based on examination of how signs, symbols and visual codes determine the underlying meaning and multi-cultural meanings incorporated in animation. Animation is a powerful form of visual storytelling that communicates complex messages through images, sound and movement. Through a qualitative research of selected animated content, this research explores how signs and symbols function in visual, auditory, and animated narratives. The study applies semiotic theoretical frameworks to analyze how animation takes advantage of iconic, indexical, and symbolic representations in communicating complex social, cultural, emotional and ideological meanings. The research findings indicate that animation's unique semiotic qualities, including its capacity for visual metaphor and abstraction—create distinctive meaning-making opportunities not available in live-action media. This research contributes to the understanding of animation not merely as entertainment but as a sophisticated communicative medium with its own semiotic grammar.